x=-12+-3y

Simple and best practice solution for x=-12+-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x=-12+-3y equation:


Simplifying
x = -12 + -3y

Solving
x = -12 + -3y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Simplifying
x = -12 + -3y

See similar equations:

| 10G+1=2k+(7X+Y) | | 5r+5-r-5= | | -3.8y=-24 | | 3(3+4)=3x+4 | | 9x^2-26x-35=0 | | 10x=x+81 | | 3x-2(x-9)=2+2x | | 4x+2x-2=12 | | 9x-3+2x-5=2(4x-1) | | 4w-1+9w= | | 5x+17+7x-29=90 | | 5x+5=5y | | 120+-4.5=120 | | 2ax^2-4(a+1)x+4a+1=0 | | 4x^4-4x^3-17x^2-19x-6=0 | | 5x+4-8=18 | | 3n^2=-4n-1 | | 5(3k+2)=40 | | 6x-5+2x+43=90 | | 3+2(x+2)=15 | | 3(2y+1)=39 | | 2x+8=x+11 | | X=-0.5x+3 | | -7(2t+8)=-126 | | r+(-016)=0.37 | | 5(f-1)=-25 | | (7a^3-2a^2-4a+9)+(3a+6)-(-a^2-a+3)= | | 14x+18y=63 | | -9(T-2)-(t+3)=2 | | x+44=4x+17 | | 2(3x+4)=2x+1 | | 8(s-7)=-92 |

Equations solver categories